11 Impact of transthoracic versus transoesophageal echocardiography measurement of vegetation length in infective endocarditis on indications for surgery. (17th July 2020) - Hoare, David; Bhattacharyya, Sanjeev; Lloyd, Guy; Young, William J; Woldman, Simon
Abstract : Introduction: Infective Endocarditis (IE) has high mortality. Longer vegetation length is associated with increased stroke risk and mortality. Guideline indications for surgery to prevent embolism are based on vegetation length. However they do not specify which modality should be used for the measurement. Transoesophageal echocardiography (TOE) imaging is only a Class I indication for prosthetic heart valves or where trans-thoracic (TTE) is inconclusive. Therefore, not all patients with IE will undergo TOE. We investigated whether there are differences in TTE and TOE measurement of vegetation length and the potential impact on indications for surgery. Methods: This was a retrospective study of 68 patients with definite endocarditis that had undergone both TOE and TTE imaging. Vegetation length was measured on two dimensional images. Indications for surgery to prevent embolism using the ESC 2015 guidelines were compared for vegetation length on TOE and TTE. Results: The median time between TTE and TOE was 2 days. 21/68 (30.8%) patients with vegetations identified on TOE were not identified on TTE. Of the remaining 47 patients, 27 (57.4%) had longer vegetations measured on TOE than on TTE with the mean difference being 7.8mm. 2/47 (4.3%) patients had the same vegetation length on TOE as on TTE. 18/47 (38.3%) patients had longer vegetations measured on TTE than on TOE with the mean difference being 4.3mm. The mean difference in vegetation length overall was 5.9mm. Of the 59 patients with left sided endocarditis, 16 cases (27.1%) would change their surgical indication based on using TOE vegetation length rather than TTE vegetation length. 11/59 (18.6%) cases would change from no indication for surgery to a class IIa indication and 5/59 (8.5%) cases would change from no indication for surgery to a class IIb indication. Conclusion: TTE often underestimates vegetation length compared to TOE. The change in vegetation length recorded between the two modalities would have changed the indication for surgery to prevent embolism in 27% patients. Measurements of vegetation length to determine surgical intervention for the prevention of embolization should be taken from TOE imaging rather than TTE. Conflict of Interest: None